AKTIVITAS DAN RELASI SOSIAL MAJELIS AGAMA BUDDHA TANTRAYANA ZHENFO ZONG KASOGATAN DI KALIMANTAN BARAT - M Taufik Hidayatulloh (Jurnal Dialog, 2015)
This study aims at firstly reporting the activities and organization structure of Tantrayana Zhenfo Kong Budhha forum Kasogatan Indonesia in West Borneo. Secondly, it is explaining the internal conflicts among Buddhists and the resolutions. The study was conducted in West Borneo in 2015 by involving the Tantrayana Zhenfo Kong Budhha forum, regional ministry office (Buddha division, community counseling of Pontianak city and Kubu Raya regency), Forum of Interreligious relation (FKUB) of West Borneo, some religious figures, and forum administrators. 12 researchers conducted this study. Data were collected through in-depth interviews and documentary study. The data were analyzed by following Miles and Huberman’s sequences, namely data reduction, data display, and conclusion. The results of this study indicate that the Budhha forum of Tantrayana Zhenfo Kong Kasogatan Indonesia has sufficient facilities in terms of houses of worship, Buddhist counseling, and children care. Additionally, it is found that there are some emerging conflicts, such as: conflicts in education and conflicts of conversion. In terms of social relationship with local people, Buddhists in west Borneo are involved in social gathering for only particular events. On the other hands, they have a relatively close relationship with the government.